Apoptotic colopathy following bendamustine therapy - Vincent Czerwinski; Wei Cui; Marc Hoffmann (Elsevier, 2023)
A 60-year-old woman with marginal zone lymphoma was treated with obinutuzumab and bendamustine after failing rituximab. She later developed intractable nausea and diarrhea which resulted in a dramatic weight loss and multiple hospitalizations. During her hospital stay the patient had a colonoscopy and biopsy which identified apoptotic colopathy- a pathologic condition characterized histologically by apoptosis. Her apoptotic colopathy was ultimately attributed to bendamustine, a previously unidentified trigger of apoptotic colopathy. The patient was eventually discharged on total parenteral nutrition (TPN) and has regained weight with adequate control of her diarrhea.